Sentidos e significados a partir de práticas de geometria na perspectiva lógico-histórica explicitados por estudantes do 6º ano em situações desencadeadoras de aprendizagem - Guimarães, Simone Uchôas (2018)
This research aims to (1) create an environment conducive to the development of Learning Displacement Situations (SDA) in the context of a classroom with 6th grade students and (2) to investigate the meanings and meanings explained by these students at from geometric practices that occurred during the development of SDA in the logic-historical perspective that consider the assumptions of the Teaching Teaching Activity (CEA). It is a qualitative and field research that was driven by the following questions: (1) what meanings and meanings arise in a group of students of the 6th grade, from an educational organization that privileges the creation of an environment for the development of SDA? (2) what meanings and meanings are explained by students of the 6th year from geometry practices present in SDA in the logical-historical perspective? The theoretical foundation considers Historical-Cultural Theory, highlighting the studies about the meanings and meanings addressed by Vigotski (2010), Leontiev's Theory of Activity (1978) and Davydov's (1982) discussions about the development of empirical thinking and theoretical. The context of the research involves a state school in a city in the interior of the state of São Paulo. The insertion of the researcher in the school occurred from May 2016 to December of the same year, and the second semester was dedicated to the development of six SDA, based on the assumptions of the AOE. SDA, audio and video recorders, student records and the researcher's field diary were used to construct the data. In the analysis of the data came two categories: (1) a new configuration of the classroom; and (2) Senses and meanings about the geometric concepts treated in the school context. During the research, the planning of actions in the classroom was intentional, so that the students had opportunities to negotiate meanings, to elaborate meanings and, consequently, to develop their theoretical thinking. By modifying the dynamics of Mathematics classes, one can perceive a certain strangeness of students, but also an openness to new proposals. The data revealed difficulties in understanding some geometric concepts, since the senses that the students gave were very much rooted in everyday, empirical or memorizing some definitions. In the end, it was realized how important this kind of work in the classroom is and the challenges that this type of approach brings.